LOCAL WISDOM-BASED LIVELIHOOD STRATEGIES OF WOMEN HOUSEHOLDS IN CENTRAL MALUKU - Ali Tutupoho; Maria Tupamahu; Hendri Dony Hahury; Lewi Batkunda; Marnex Bokaraman (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2021)
This study examines women’s activities which include production and reproduction activities in several economic sectors as a source of livelihood for the women in negeri Booi community. This study was done in a qualitative manner with a phenomenological approach, integrated with an institutional economic perspective in negeri Booi, Saparua island, Central Maluku. The key informants participated in this study were women who collected nutmeg, owners of dusung (garden), and saniri negeri (village government). The data was collected through in-depth interviews, observations and documentation. The results show that the activities done by the rural women in an effort to meet their household needs were production, reproduction, and access and control of resources. Further, local wisdom or tradition also played an important role in carrying out these activities, including bapilih tradition. It was a dominant factor influencing the efforts to meet the women’s household needs in negeri Booi. In addition, the bapilih tradition was also an effort of the negeri Booi community to save the poor from unsafe to safe conditions which were motivated by the tradition. Apart from being a “buffer”, the bapilihtradition had been an “informal insurance” for the women in negeri Booi to be able to carry out the activities to meet their household needs although the dusung was not theirs.